Advances in structural adhesive bonding - Dillard, David A. (Woodhead Publishing series in welding and other joining technologies., 2010)
Adhesive bonding is often effective, efficient, and often necessary way to join mechanical structures. This important book reviews the most recent improvements in adhesive bonding and their wide-ranging potential in structural engineering. Part one reviews advances in the most commonly used groups of structural adhesives with chapters covering topics such as epoxy, polyurethane, silicone, cyanoacrylate, and acrylic adhesives. The second set of chapters covers the various types of adherends and pre-treatment methods for a range of structural materials such as metals, composites and plastics. Chapters in Part three analyse methods and techniques with topics on joint design, life prediction, fracture mechanics and testing. The final group of chapters gives useful and practical insights into the problems and solutions of adhesive bonding in a variety of hostile environments such as chemical, wet and extreme temperatures. With its distinguished editor and international team of contributors, Advances in structural adhesive bonding is a standard reference for structural and chemical engineers in industry and the academic sector. Reviews advances in the most commonly used groups of structural adhesives including epoxy, silicone and acrylic adhesivesExamines key issues in adhesive selection featuring substrate compatibility and manufacturing demandsDocuments advances in bonding metals, plastics and composites recognising problems and limitations.